Biocatalytic synthesis of highly ordered degradable dextran-based hydrogels - Ferreira, Lino (2005)
We have prepared unique macroporous and ordered dextran-based hydrogels using a single-step biocatalytic transesterification reaction between dextran and divinyladipate in neat dimethylsulfoxide. These hydrogels show a unimodal distribution of interconnected pores with average diameters from 0.4 to 2.0 [mu]m depending on the degree of substitution. In addition, the hydrogels show a higher elastic modulus for a given swelling ratio than chemically synthesized dextran-based hydrogels. In vivo studies in rats show that the hydrogel networks are degradable over a range of time scales from 5 to over 40 days, and possess good biocompatibility, as reflected in only a mild inflammatory reaction and minor fibrous capsule formation during the time-frame of subcutaneous implantation. These combined properties may offer competitive advantages in biomedical applications ranging from tissue engineering to controlled drug delivery.